2001
DOI: 10.1007/pl00004186
|View full text |Cite
|
Sign up to set email alerts
|

Competitive and core allocations in large economies with differential information

Abstract: Summary.We study the core and competitive allocations in exchange economies with a continuum of traders and differential information. We show that if the economy is "irreducible", then a competitive equilibrium, in the sense of Radner (1968Radner ( , 1982, exists. Moreover, the set of competitive equilibrium allocations coincides with the "private core" (Yannelis, 1991). We also show that the "weak fine core" of an economy coincides with the set of competitive allocations of an associated symmetric information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 7 publications
(13 reference statements)
0
28
0
Order By: Relevance
“…It follows from the continuity of U i (ω, x) in x and measurability in ω that U i (·, ·) is jointly measurable. Hence, under (A.2) and (A.3), the associated continuum economy E c satisfies all the assumptions of the equivalence theorem of Radner equilibria and private core (see Einy et al, 2001). …”
Section: Radner Equilibria In Continuum Economiesmentioning
confidence: 96%
See 1 more Smart Citation
“…It follows from the continuity of U i (ω, x) in x and measurability in ω that U i (·, ·) is jointly measurable. Hence, under (A.2) and (A.3), the associated continuum economy E c satisfies all the assumptions of the equivalence theorem of Radner equilibria and private core (see Einy et al, 2001). …”
Section: Radner Equilibria In Continuum Economiesmentioning
confidence: 96%
“…The argument is not straightforward and requires the private core-equivalence theorem (Einy et al, 2001). However, our proof has a big payoff.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, one can follow Radner (1968) and impose the requirement that an agent's trades be measurable with respect to her private information. Equilibrium allocations so defined bear the standard relationship with the private core (see Section 1.1.3), which similarly imposes such measurability restrictions; see Einy et al (2001a). 37 When the economy is replicated in the way proposed by Gul and Postlewaite, on the other hand, each individual's information remains private even in the large economy and we need a notion of competitive equilibrium which takes incentives into account.…”
Section: The Ex Ante Corementioning
confidence: 99%
“…Throughout the paper we assume that for all t ∈ T and ω ∈ Ω the function u t (ω, ·) is strictly increasing and continuous on l Einy, Moreno and Shitovitz (1998) have shown that if the utility functions of the traders are continuous and strictly increasing, and if every commodity is present in the market (i.e., T e(t, ω)d µ 0 for all ω ∈ Ω), then a competitive equilibrium (in the sense of Radner) exists when the economy is irreducible (see Theorem A in Einy, Moreno and Shitovitz, 1998). Since in our model the initial endowments of the traders are in l ++ , the economies we consider here are irreducible (see Proposition 3.1 in Einy, Moreno and Shitovitz, 1998), and therefore always have a competitive equilibrium.…”
Section: ω)mentioning
confidence: 99%